POPULATION ANALYSIS IN ATLANTIC THREAD HERRING FROM THE BRAZILIAN COAST - Cleonilde Queiroz; Maria Iracilda da Cunha Sampaio; Horacio Schneider (Revista Eletrônica Científica Ensino Interdisciplinar, 2020)
The Atlantic thread herring Opisthonema oglinum, also known as Bermuda herring belongs to the family Clupeidae (Clupeiformes). Because of their economic and ecological importance, this species has been the target of several scientific studies. However, this is the first study of population genetics in O. oglinum. We sampled individuals of O. oglinum from seven localities along the Brazilian coast in South Atlantic, totaling 225 DNA sequences of control region in mitochondrial DNA (mtDNA). The present results revealed no deviations from Hardy-Weinberg equilibrium as well as the presence of a single gene pool since high gene flow and non-significant population structure have been detected among populations. The D (Tajima) and Fs (Fu) neutrality tests were negative. In spite of non-significant D values, all Fs estimates were significant, indicating population expansion.